2016
DOI: 10.1093/cz/zow082
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity can explain evolution of sympatric polymorphism in the hairy snailTrochulus hispidus(linnaeus, 1758)

Abstract: Morphological variation of snails from the genus Trochulus is so huge that their taxonomy is unclear. The greatest variability concerns forms hispidus and sericeus/plebeius, which are often considered as separate species. To evidence the species barriers, we carried out crossbreeding experiments between these two sympatric morphs. Moreover, we compared the shell morphology of laboratory-bred offspring with their wild parents to test if the variation can be explained by the phenotypic plasticity model. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…Disregarding the incorrect assignment of the samples, these results can be interpreted into two ways. Following our previous findings, showing the influence of local environment on shell shape in Trochulus taxa (Proćków et al, 2017a(Proćków et al, , 2017b(Proćków et al, , 2018, we can assume that these outstanding cases represent individuals genetically related with others in the population but having different shell morphology due to such a phenotypic plasticity and the environmental influence. It means that the same or similar shell morphology can occur independently in different genetic lineages.…”
Section: Intermixed Specimenssupporting
confidence: 68%
See 1 more Smart Citation
“…Disregarding the incorrect assignment of the samples, these results can be interpreted into two ways. Following our previous findings, showing the influence of local environment on shell shape in Trochulus taxa (Proćków et al, 2017a(Proćków et al, , 2017b(Proćków et al, , 2018, we can assume that these outstanding cases represent individuals genetically related with others in the population but having different shell morphology due to such a phenotypic plasticity and the environmental influence. It means that the same or similar shell morphology can occur independently in different genetic lineages.…”
Section: Intermixed Specimenssupporting
confidence: 68%
“…Moreover, recent studies have provided an even more confusing picture, revealing that T. sericeus/hispidus constitutes a complex of morphologically similar but genetically divergent species in the Sarine valley in Swiss Western Prealps (Dépraz et al, 2009) and the snails morphologically resembling T. sericeus sometimes form genetically separate clades (Duda et al, 2014;Proćków et al, 2014Proćków et al, , 2017c or conversely, two morphologically different shells assigned to T. hispidus and T. sericeus do not form phylogenetically distinct clades (Duda et al, 2014;Proćków et al, 2013); hence, these snails are often described as the T. hispidus complex (Kruckenhauser et al, 2014). Furthermore, T. hispidus and T. sericeus appeared to be phenotypically plastic and showed no interbreeding constraints (Proćków et al, 2017a). Since their shell morphology strictly depends on microhabitat, they were regarded ecophenotypes (Proćków et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Arboreal species tend to have a narrow umbilicus and a relatively tall shell, while ground‐dwelling species have a wide umbilicus and flat shell (Hirano, Kameda, Kimura, & Chiba, 2015). In contrast, the variation of umbilicus width could also be a result of phenotypic plasticity (Proćków, Kuźnik‐Kowalska, & Mackiewicz, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports (e.g., Hausdorf, 1998;Hirano et al, 2014;Hyman et al, 2017) have suggested that genital traits are more likely to reflect the actual phylogenetic relationships than morphological appearances. On one hand, phenotypic plasticity in snail shells is a well-documented phenomenon and is probably a response to environmental variation (Emberton, 1991(Emberton, , 1995Gustafson et al, 2014;Proćków et al, 2017). The other is convergence and parallelism in the character states of the shell morphology and other anatomical structures that are generally known in land snails (Hirano et al, 2014(Hirano et al, , 2015Köhler & Criscione, 2015;Hyman et al, 2017).…”
Section: Phylogeny and Taxonomic Implicationsmentioning
confidence: 99%